2018
DOI: 10.1371/journal.pone.0201650
|View full text |Cite
|
Sign up to set email alerts
|

Human iPS cell-derived cardiac tissue sheets for functional restoration of infarcted porcine hearts

Abstract: To realize human induced pluripotent stem cell (hiPSC)-based cardiac regenerative therapy, evidence of therapeutic advantages in human-sized diseased hearts are indispensable. In combination with an efficient and simultaneous differentiation of various cardiac lineages from hiPSCs and cell sheet technology, we aimed to generate clinical-sized large cardiac tissue sheets (L-CTSs) and to evaluate the therapeutic potential in porcine infarct heart. We simultaneously induced cardiomyocytes (CMs) and vascular cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…A research group successfully used the fibrin gel-enhanced delivery of human iPSC-CM sheet to decrease cardiac infarction at 4 weeks after transplantation via vascularity, to decrease apoptosis, and to increase engraftment rates in a mouse model at 4 weeks of MI [76]. Recently, clinical-sized large CTSs composed of 32.4-58.8% CMs, 0.9-9.7% endothelial cells, and 6.3-35.1% MCs were created by Ishigami and his colleagues [77]. They confirmed that L-CTS transplantation attenuated left ventricular remodeling and improved cardiac dysfunction with higher systolic function of the left ventricular, higher ejection fraction of the left ventricular, increased circumference strain in infarct border regions, lower fibrotic area, and higher capillary density in the border region at 4 weeks after transplantation in a 6-week AMI porcine model [77].…”
Section: Pluripotent Stem Cell-derived Cell Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…A research group successfully used the fibrin gel-enhanced delivery of human iPSC-CM sheet to decrease cardiac infarction at 4 weeks after transplantation via vascularity, to decrease apoptosis, and to increase engraftment rates in a mouse model at 4 weeks of MI [76]. Recently, clinical-sized large CTSs composed of 32.4-58.8% CMs, 0.9-9.7% endothelial cells, and 6.3-35.1% MCs were created by Ishigami and his colleagues [77]. They confirmed that L-CTS transplantation attenuated left ventricular remodeling and improved cardiac dysfunction with higher systolic function of the left ventricular, higher ejection fraction of the left ventricular, increased circumference strain in infarct border regions, lower fibrotic area, and higher capillary density in the border region at 4 weeks after transplantation in a 6-week AMI porcine model [77].…”
Section: Pluripotent Stem Cell-derived Cell Sheetmentioning
confidence: 99%
“…Recently, clinical-sized large CTSs composed of 32.4-58.8% CMs, 0.9-9.7% endothelial cells, and 6.3-35.1% MCs were created by Ishigami and his colleagues [77]. They confirmed that L-CTS transplantation attenuated left ventricular remodeling and improved cardiac dysfunction with higher systolic function of the left ventricular, higher ejection fraction of the left ventricular, increased circumference strain in infarct border regions, lower fibrotic area, and higher capillary density in the border region at 4 weeks after transplantation in a 6-week AMI porcine model [77]. Considering the substantial advantages of unlimited proliferation ability and directional differentiation function, iPSC-CMs could be the most feasible cell source for myocardial cell therapy for clinical MI.…”
Section: Pluripotent Stem Cell-derived Cell Sheetmentioning
confidence: 99%
“…More recently, Kawamura et al took a rather unprecedented approach to enhance survival and engraftment of transplanted human iPSC-CMs by combining cell-sheets with pedicle omentum flap as a source of angiogenic factors and reported enhanced engraftment, survival, and therapeutic outcome in a porcine model of ischemic cardiomyopathy [217,218]. The aforementioned tissue sheet technology from Kyoto was also recently applied to a porcine model of MI, where a heterogeneous mixture of cardiovascular cell populations differentiated from human iPSCs and reported functional restoration of the infarcted hearts and attenuated remodeling [219]. Another study from 2018 by Gao and colleagues reported the application of human iPSC-derived fabricated cardiac muscle patches (hCMPs) composed of CMs, smooth muscle and endothelial cells, reprogramed from cardiac fibroblasts and maturated in dynamic culture conditions [220].…”
Section: Porcine Modelsmentioning
confidence: 99%
“…Recently, stem cells usage has been known as an attractive method, which could regenerate and repair the lost heart organ [6]. Nowadays, broadly used cells in the animal modeling are modeling that are somatic stem cells from various adult tissues, embryonic stem (ES) cells, and induced pluripotent stem (iPS) cells [7,8]. As mentioned earlier, somatic stem cells-derived from various tissues such as adipose tissue, bone marrow (BM), and heart have been used to regenerate dead myocardium; however, its efficiency is low due to progressive loss of functional role and reduced output [9].…”
Section: Introductionmentioning
confidence: 99%